(untitled) (Research, Society and Development, 2021)
Melamine-formaldehyde based composites are versatile and can be applied in the treatment of contaminated effluents such as landfill leachate that have a high pollutant load, as they are rich in nitrogen atoms, the sites allow interaction with molecules, atoms or ions of interest. Aiming compares the efficiency of two materials based on the same precursors, evaluating the efficiency of two composites, melamine-silica (PMF-Si) and melamine-silica-cellulose (Cel-M-Si) in removing iron and ammonia nitrogen in landfill leachate. Adsorption kinetics showed that PMF-Si and Cel-M-Si composites adsorb iron from 30 min, with an average removal of 93.4%. Application of Cel-M-Si to removed leachate ca. 75.7% iron and 76.6% ammonia nitrogen. In contrast, it was observed that PMF-Si had a removal efficiency of 70.9% for iron and 55.0% for ammonia nitrogen. The comparative tests allowed to conclude that the composites PMF-Si and Cel-M-Si have potential for the treatment of landfill leachate, being low cost materials and easy synthesis.